HAK ASASI PEREMPUAN DALAM KONSTITUSI DAN KONVENSI CEDAW - Nuraida Jamil (UIN K.H. Abdurrahman Wahid Pekalongan, 2014)
Women's Rights are rights held by a woman, because she was a human being and as a woman who has the dignity of humanity. Women's rights are part of human rights. As part of Human Rights, the Rights of Women is also provided in the Constitution is the Constitution of the Republic of Indonesia in 1945. In particular, Women's Rights set in CEDAW which was ratified by the government through Act No. 7 of 1984 on ratification of the Convention on the Elimination of All Forms of Discrimination against Women. Regulation on Rights of Women, giving responsibility and requires the state to respect, to protect and to fulfill the rights of Women. Hak-Hak Perempuan adalah hak yang dimiliki oleh seorang wanita, karena dia manusia dan sebagai seorang wanita yang memiliki martabat kemanusiaan. Hak-hak perempuan adalah bagian dari hak asasi manusia. Sebagai bagian dari Hak Asasi Manusia, Hak Perempuan juga disediakan dalam Konstitusi Undang-Undang Dasar Negara Republik Indonesia tahun 1945. Secara khusus, Hak-Hak Perempuan diatur dalam CEDAW yang telah diratifikasi oleh pemerintah melalui Undang-Undang Nomor 7 Tahun 1984 tentang ratifikasi konvensi Penghapusan Segala Bentuk Diskriminasi terhadap Perempuan. Regulasi tentang Hak Perempuan, memberikan tanggung jawab dan membutuhkan negara untuk menghormati, melindungi dan memenuhi hak-hak perempuan